THE DANCE OF LACK: THE UNVEILING OF THE REAL IN PINA BAUSCH'S DANCE - Fernandes Moreira, Greta; Bernardo Fuks, Betty (Revista de Psicologia, 2023)
This article aims to investigate what would be the effects of unveiling the real on stage for the spectator of modern and contemporary dance by analyzing, in line with psychoanalytic theory, the work Kontakthof (1978) by the German dancer and choreographer Pina Bausch, founder of the Tanztheather Wuppertal, who revolutionized contemporary dance, by bringing to the stage the subjectivity of each dancer, awakened through a creation process that is peculiar to her, and which allows her to establish a direct connection with the spectator, by evoking such feelings as shock and estrangement (unheimlich), which can also be understood as a display of anguish, an edge phenomenon, which signals this last limit prior to the real and the field of jouissance.